Monitoring of the state of atmospheric air of the airport zone on the grounds of researches of precipitations - Франчук, Г.М.; Антонов, А.М.; Маджд, С.М.; Рахімбердіна, Н.В. (Proceedings of National Aviation University, 2005)
The estimation of a condition of precipitations of a zone of the airport is carried out and contents in them of pollutants are determined. The results of biotesting on detection of toxicity in tests of a hibernal snow level of the zone of airport are adduced. The relation of a level of pollution to term of stay of a snow in the airport zone and remoteness from the airport is determined.